A telepathology based screening tool for COVID-19 by leveraging morphological changes related to leukocytes in peripheral blood smears - K Anil Savitha; Vara Prasad; K H Manjunath; E Nair Govind; S Jagadish Manjula; Ethirajan Renu; R Arcot Lokanathan; Dixit Neha; Ravichandhren Shanthinee; R Dastidar Tathagato (Wolters Kluwer Medknow Publications, 2022)
As we approach the aftermath of a global pandemic caused by Severe Acute Respiratory Syndrome-Corona Virus (SARS-CoV-2), the importance of quickly developing rapid screening tests has become very clear from the point of view of containment and also saving lives. Here, we present an explorative study to develop a telepathology-based screening tool using peripheral blood smears (PBS) to identify Coronavirus Disease (COVID-19)-positive cases from a group of 138 patients with flu-like symptoms, consisting of 82 positive and 56 negative samples. Stained blood smear slides were imaged using an automated slide scanner (AI 100) and the images uploaded to the cloud were analyzed by a pathologist to generate semi-quantitative leukocyte morphology-related data. These telepathology data were compared with the data generated from manual microscopy of the same set of smear slides and also the same pathologist. Besides good correlation between the data from telepathology and manual microscopy, we were able to achieve a sensitivity and specificity of 0.83 and 0.71, respectively, for identifying positive and negative COVID-19 cases using a six-parameter combination associated with leukocyte morphology. The morphological features included plasmacytoid cells, neutrophil dysplastic promyelocyte, neutrophil blast-like cells, apoptotic cells, smudged neutrophil, and neutrophil-to-immature granulocyte ratio. Although Polymerase Chain Reaction (PCR) and antibody tests have a superior performance, the PBS-based telepathology tool presented here has the potential to be an interim screening tool in resource-limited settings in underdeveloped and developing countries.